Hubungan Beban Kerja dan Stres Kerja dengan Produktivitas Kerja di Bagian Produksi PT Andalas Dolomite Sejahtera Tanjung Lolo Sijunjung Tahun 2024 - Ikbal, Revi Neini; Said, Faridah Mohd. (Alifah Health Science Symposium Proceeding, 2024)
Spiritual needs are basic needs that must be met by patients, especially patients in intensive care in the intensive care unit (ICU). In hospitals, the implementation of fulfilling spiritual needs is still very neglected. Patients who get their spiritual needs fulfilled will experience more peace and better outcome during treatment. Fulfilment of spiritual nursing services can be provided by nurses who work in the intensive care unit, including prayer, dhikr and prayers. Objectives: This study aims to explore the experiences of nurses in the intensive care unit in meeting the spiritual needs of patients treated in the intensive care unit (ICU). This research uses a qualitative descriptive exploration method. Participants in this study were 14 nurses with the inclusion criteria being ICU nurses. The theme analysis used in this research is the Miles da Huberman Technique. Results qualitative data analysis yielded three main themes supported by seven categories, namely The first theme of the patient's spiritual needs which consisted of 2 categories, namely giving and fulfillment. The second theme is facilities which consist of 2 categories, namely the outer spiritual team and the inner spiritual team. The third theme of hope consists of patients, families and nurses.This study concludes that there are 3 themes generated in the nurse's experience of fulfilling spiritual needs in the ICU room, namely the patient's spiritual needs, spiritual team facilities and expectations.